Sintering and optical quality of highly transparent yb‐doped yttrium lanthanum oxide ceramics. Issue 6 (2nd May 2013) - Ivanov, Maxim; Kopylov, Yury; Kravchenko, Valery; Zayats, Sergey; Palashov, Oleg V.; Khazanov, Efim A.; Kravchenko, Valery B.; Fedorov, Pavel P.
Abstract To produce highly transparent Yb‐doped yttrium lanthanum oxide (Yb3+:(LaxY1–x)2O3) ceramics two original technologies were used: laser synthesis of nanopowder and pulsed magnetic compacting. Sintering of the compacts in vacuum 3×10–4 Pa at 1600–1700 °C during 13 hours led to transparent ceramics fabrication. The ceramics with relative density higher than 99.99% and grain size about 40 µm were fabricated. Full transmittance of 1.8 mm thick Yb0, 11La0, 23Y1, 66O3 ceramics reaches 82.5%@800 nm. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)